Incidencia del consumo del alcohol en las conductas agresivas de los estudiantes del segundo año de bachillerato paralelo a, de la Unidad Educativa Manuel Ignacio Monteros Valdivieso, 2020-2021. - Garrido Quizhpe, Jhanina Magdali (2022)
The objective of this research was to determine the incidence of alcohol consumption in the aggressive behaviors of students in the second year of high school parallel "A" of the Manuel Ignacio Monteros Valdivieso Educational Unit 2020-2021. It was a quantitative research, of descriptive type, and non-experimental design, of transversal cut. The methods used were: the scientific, analytical, synthetic, deductive, inductive and statistical method. The Alcohol Expectancy Questionnaire (AEQ-A) and the Buss and Perry AQ Questionnaire were applied to a sample of 21 students. The results obtained in relation to alcohol consumption indicate that 47.6% of the students have high levels of relaxation and social assertiveness; likewise, 52.4% show medium levels of verbal aggressiveness in aggressive behaviors. In view of the above results, it is concluded that those investigated have positive expectations to consume alcohol, and also show aggressive verbal behaviors, so it is determined that there is an incidence, i.e. adolescents who consume alcohol are prone to show aggressive behaviors. In view of this, it is recommended that the authorities and the Student Counseling Department (DECE) include in the Annual Operational Plan (POA) issues of alcohol consumption, aggressive behaviors and their incidence, in order to ensure that these issues are addressed permanently and continuously in the educational institution. Key words: adolescents, alcohol consumption, aggressive behaviors.